Rapid detection of Mycoplasma pneumoniae by loop-mediated isothermal amplification assay. Issue 25 (June 2018) - Yuan, Xin; Bai, Changqing; Cui, Qian; Zhang, Han; Yuan, Jing; Niu, Kaiwen; Feng, Yuzhong; Jin, Xin; Li, Puyuan; Liu, Huiying
Abstract : Abstract: To improve the diagnosis and treatment of Mycoplasma pneumoniae (Mp) infection and reduce the misuse of antibiotics, we sought to establish a loop-mediated isothermal amplification (LAMP) assay for rapid detection of Mp. Six primers specific for the Mp P1 gene were designed, and the LAMP method was used to rapidly detect Mp. The sensitivity of the LAMP method was determined by serial dilution of the standard Mp strain FH (standard strains of Mycoplasma pneumoniae). Specificity was assessed with 17 common pathogenic microorganisms in the respiratory tract. Patient samples were collected from the Department of Respiratory and Critical Care Medicine at the 307th Hospital of Chinese People's Liberation Army from March 2016 to May 2017, examined prospectively, and compared with diagnosis by quantitative real-time polymerase chain reaction (qRT-PCR). The LAMP assay for Mp detection can be completed within 60 minutes. The minimum detection limit was 39 pg/μL, and no cross-reaction was observed with 17 common respiratory tract pathogens. Of the 125 clinical specimens tested, 43 cases were positive by LAMP assay, and 40 cases were positive by qRT-PCR ( P = .162). All 43 samples determined as positive by LAMP test were confirmed to be Mp by Mp P1 protein sequencing. The LAMP assay is suitable for rapid detection of Mp. It has high sensitivity and specificity, and the detection results are not inferior to those of qRT-PCR.